Analiza šolske ure pouka književnosti po modelu analize govorjenega diskurza - Pirih Svetina, Nataša (Jezik in slovstvo, 1999)
The model of discourse analysis is applied to discourse observed during an eighth grade literature class. The study aims at exploring what this type of analysis can tell about the quality of classroom work and the quality and ratios of speech of individual participants in the communication. A long-term objective of this research is to explore how these could be implemented in changing and possibly improving spoken interaction during literature class.
Keywords: Slovene; slovenščina; didactic method; didaktika; tekstna lingvistika; analiza diskurza; osnovne šole